Mezinárodní srovnání výkonnosti zdravotnictví ve visegradských zemích - Dlouhý, Martin (Casopis lekaru ceskych, 2016)
The objective of this study is to evaluate performance of the health systems in Visegrad countries - the Czech Republic, Hungary, Poland, and Slovakia. For a comparison, Austria and Germany are included, as they represent Western European countries neighbouring with the Visegrad countries. The health system performance is evaluated by six different measures.In spite of the fact, that methodologies, sets of countries, and time periods differ, we observe very similar findings. The Czech Republic has the best performing health system from the Visegrad countries, and Hungary looks like having the worst performing health system. In case of Poland, the indicators based on subjective view of population show worse performance of the health system than the other more objectively oriented indicators. It seems that Polish people view the health system too negatively in comparison with its real performance. If Germany and Austria are included in the comparison, we observe an existing gap between these two Western European countries and Visegrad countries.Key words: health system performance, Visegrad countries, international comparison.
Keywords: Czech Republic; Německo; Humans; Maďarsko; Slovenská republika; Hungary; lidé; internacionalita; Internationality; Poland; Česká republika; Germany; Patient Satisfaction; Rakousko; Quality of Health Care; Polsko; Slovakia; kvalita zdravotní péče; spokojenost pacientů; Austria